Microatlas linguístico contatual das variedades do português falado no norte de Mato Grosso - Marques, Maria José Basso (2022)
The northern region of Mato Grosso is characterized by the sociocultural heterogeneity and linguistic diversity. The settlement movements that shaped this space in the 1970s, coming from various regions of Brazil, especially from the southern states, provided the locus of varied linguistic contacts - between different languages and/or between varieties of the same language. This scenario motivated this research, which, based on the theoreticalmethodological principles of Pluridimensional and Relational Dialectology, sought to describe the semantic-lexical and phonetic-phonological aspects of the linguistic varieties of the Portuguese spoken in contact situations in the North of Mato Grosso, inferring the elements of maintenance and innovation of this variation in five municipalities: Colíder, Nova Canaã do Norte, Itaúba, Terra Nova do Norte and Nova Santa Helena, in the form of a Contactual Linguistic Microatlas of the North of Mato Grosso – CONLMALMAT (MALCONMAT in Portuguese). Data collection was carried out through a questionnaire that addressed linguistic issues: phonetic, lexical and sociocultural. At each point, 08 (eight) subjects were surveyed, totaling 40. The selection of informants considered the following dimensions: diatopic (topodynamic and topostatic); the diageneric (male and female); diastratic (low education), dialingual/contact (intervarietal contact, Gaucho Portuguese, GP (PG in Portuguese - Gaucho is typical from people of Rio Grande do Sul state), and Caipira Portuguese, CP (PC in Portuguese – Caipira is typical from people of the north of Parana state); the diagenerational that consisted of two age groups, one older (GII), over 50 years old, migrants, living in the locality for more than twenty years, and the young (GI), from 18 to 40 years old, children of migrants, born and residing in the investigated location; the diaphasic (speech styles) and the diareferential (linguistic comments). The data revealed that the intervarietal contact, which took place in this territory, is in the process of linguistic leveling, occurring in a gradual and variable way, revealing the formation of a coiné with marks of Caipira Portuguese.